THE LANGUAGE BEHAVIOUR ON KINSHIP ADDRESSES BY JAVANESE SPEAKERS - Sugeng Trijanto; Hamzah A. Mahmoed; Martin L. Manda; Mustafa Makka (Musamus Journal of Language and Literature, 2020)
The various kinship address pairs are found in the domain of a nuclear family in relationships a husband and wife namely bapak-ibu, mas-dik, bapak-emak, bapak-mbok, ayah-ibu, bapak/ayah/mas-a nick name of child or a nick name of a wife. The factors influence the uses of this pair are not only sex but also the speaker’s status such as economy, education, etc; city or rural areas, speaker’s mobility, speaker’s opinion, familiarity, prestigious, education, and meaning which contains in a kinship address. In this husband-wife relationship, social attributes are commonly used by a husband to his wife and by a wife to her husband, contrast to English speakers in western countries. Then, the use of dedek is because of age for small children but mas/mbak, dik, pak/bulek, pak/bude, etc are because of other partisipants in nuclear and extended families. Mbah in an extended family and non-family is not completely age to be considered in usage but putu or grandchild. In various nuclear families, mas/mbak-dik appears in the family whose (a) parent(s) profession are/is (a) teacher(s) on Islamic lesson and their activity in Islam whereas others who have different profession and activity use mas/mbak-proper name and family in the lowest class does not use these social attributes at all. Furthermore, this research also reveals that ngajari not only for educating smooth language to small children but also for educating the uses of kinship addresses to small children, children, and teens who are involved or not involved in the communication. Finally, the kinship addresses are chosen based on socio, pragmatic, and religious factors which are the culture of Javanese speakers.